Effects of metamitron under different relative humidity conditions on the fruit abscission of Malus domestica Borkh. cultivars - Rosa, Nídia (2020)
Metamitron is an apple (Malus domestica Borkh.) fruit thinner that acts by reducing the photosynthetic capacityof trees. Relativehumiditymayinfluence thinningefficacy; however, thebroadness of this effect is not yet fully understood. Trials were set in Sint-Truiden (Belgium) in 2018 and Lleida and Girona (Spain) in 2019, using 4-year-old cvs. Braeburn and Elstar trees in Belgium, and 16-year-old cv. GoldenReinders trees in Spain. Four treatmentswere implemented at the stage of 12–14mmfruit diameter: (a) CTR—control, trees under natural environmental conditions; (b) HH—high humidity, trees submitted to artificially increased air relative humidity applied for 3 h prior to the beginning of the experiment; (c)MET—trees sprayedwith 247.5mg/Lmetamitron; (d)MET + HH—trees submitted to the combination of increased humidity (HH) and metamitron (MET) application. In Belgium, metamitron absorption by leaves was greater than in Spain. This might be related to morphological characteristics of the leaves which developed under greater natural relative humidity levels in Belgium than in Spain. Compared to MET alone, ‘Braeburn’ and ‘Elstar’ demonstrated significantly greater metamitron absorption, 59% and 84%, respectively, underMET + HH, accompanied by declines in leaf net photosynthesis (10% and 32%, respectively) and sucrose (31% and 26%, respectively). At harvest,MET + HH treatment reduced yield by 24% and 32% in ‘Braeburn’ and ‘Elstar’, respectively, when compared withMET alone. A large reduction (considered over thinning) in the yield of ‘Elstar’ occurred. In contrast,metamitron absorption by ‘Golden Reinders’ usingMET alone was similar toMET + HH; however, there was a slight foliar sugar reduction in the latter treatment. In addition, both treatments enhanced shoot growth and increased fruit abscission with similar improvements in fruit weight and size. In this study, high relative humidity enhanced fruit thinning efficacy under certain circumstances, such as age or genetic predisposal, which left the tree more susceptible to a negative carbohydrate balance. For instance, ‘Braeburn’ and ‘Elstar’ were easier to thin when compared to ‘Golden Reinders’. In addition, this study raises a question that requires further research regarding the impact of HH before and after spraying as well as its effect in combination with higher temperatures